Effect of vasoactive intestinal polypeptide and somatostatin on secretion of epidermal growth factor and bicarbonate from Brunner's glands. Issue 11 (November 1984) - Kirkegaard, P; Olsen, P S; Nexø, E; Holst, J J; Poulsen, S S
Abstract : The effect of VIP and somatostatin on secretion of epidermal growth factor and bicarbonate from Brunner's glands was investigated in the rat. Vasoactive intestinal polypeptide infused in doses of 10 and 100 ng/kg/h significantly increased epidermal growth factor and bicarbonate output, but the concentrations did not change. Somatostatin infused at doses of 1, 10, 100 and 1000 ng/kg/h against a background of VIP 100 ng/kg/h inhibited in dose-dependent fashion the stimulated epidermal growth factor and bicarbonate outputs from rat Brunner's gland pouches. Also basal secretion was inhibited by somatostatin. Infusion of antisomatostatin serum stimulated Brunner's gland secretion. By immunohistochemical studies of rat duodena, it was found that epidermal growth factor, is almost exclusively present in the secretory cells of Brunner's glands. It is concluded that VIP stimulates secretion of epidermal growth factor and bicarbonate from Brunner's glands, an effect which is inhibited by somatostatin. A possible role for somatostatin in the control of Brunner's gland secretion is suggested.